Pendidikan Kesehatan Pencegahan Kegawatdaruratan Kehamilan Unsafe Abortion pada Remaja - Ulaa, Mar'atun; Marlin, Rizka; Azmi, Khusnul Tisa (Journal of Telenursing (JOTING), 2023)
This study aims to determine the effectiveness of educational videos on teenagers' knowledge about unsafe abortion. The method used was a quasi-experiment with a nonequivalent pretest-posttest non-control group design, which was carried out in July 2022 at IKesT Muhammdiyah Palembang with a sample of 65 people who were given health education about preventing pregnancy emergencies. The results of the research show that statistically, health education can avoid emergencies of pregnancy; unsafe abortion in adolescents is effective in increasing respondents' knowledge with a p-value of 0.000. Conclusion: Educational videos can increase teenagers' knowledge about unsafe abortion Keywords: Video Education, Pregnancy Emergency, Adolescents, Unsafe Abortion